2011
DOI: 10.1016/j.neulet.2011.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Clavulanic acid increases dopamine release in neuronal cells through a mechanism involving enhanced vesicle trafficking

Abstract: Clavulanic acid is a CNS-modulating compound with exceptional blood-brain barrier permeability and safety profile. Clavulanic acid has been proposed to have anti-depressant activity and is currently entering Phase IIb clinical trials for the treatment of Major Depressive Disorder (MDD). Studies have also shown that clavulanic acid suppresses anxiety and enhances sexual functions in rodent and primate models by a mechanism involving central nervous system (CNS) modulation, although its detailed mechanism of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…Further, the development of behavioral sensitization to morphine is thought to be more dependent on glutamate transmission than on dopamine transmission (Vanderschuren and Kalivas, 2000). Although it is somewhat difficult to reconcile the behavioral effects of CA observed here with its dopamine-enhancing effects (Sanna et al, 2013; Kost et al, 2011, 2012), it should be noted that our study used a dosing paradigm in which CA was administered repeatedly. This dosing paradigm was used because multiple laboratories have demonstrated that the preclinical activity of CTX in reducing the symptoms of CNS diseases is dependent on repeated administration (Rothstein et al, 2005; Sari et al, 2009, 2013; Rawls et al, 2007, 2010a, b; Tallarida et al, 2013; Trantham-Davidson et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Further, the development of behavioral sensitization to morphine is thought to be more dependent on glutamate transmission than on dopamine transmission (Vanderschuren and Kalivas, 2000). Although it is somewhat difficult to reconcile the behavioral effects of CA observed here with its dopamine-enhancing effects (Sanna et al, 2013; Kost et al, 2011, 2012), it should be noted that our study used a dosing paradigm in which CA was administered repeatedly. This dosing paradigm was used because multiple laboratories have demonstrated that the preclinical activity of CTX in reducing the symptoms of CNS diseases is dependent on repeated administration (Rothstein et al, 2005; Sari et al, 2009, 2013; Rawls et al, 2007, 2010a, b; Tallarida et al, 2013; Trantham-Davidson et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…Some of the effects of CTX are prevention of analgesic tolerance and physical dependence that develops during chronic morphine exposure (Rawls et al, 2007, 2010a, b), inhibition of opioid-induced hyperalgesia (Chen et al, 2012), inhibition of relapse to cocaine seeking (Knackstedt et al, 2010; Sari et al, 2009), inhibition of the direct reinforcing effects of cocaine in mice maintained under a progressive-ratio responding schedule (Ward et al, 2011), inhibition of locomotor sensitization produced by cocaine and amphetamine (Tallarida et al, 2013; Sondheimer and Knackstedt, 2011; Rasmussen et al, 2011), prevention of methamphetamine-induced CPP (Abulseoud et al, 2013), and reduction of alcohol consumption (Sari et al, 2013; Rao and Sari, 2012). Despite structural similarities between CA and CTX, and the more favorable pharmacokinetic and physiochemical properties of CA as related to CNS activity (Nakagawa et al, 1994; Bolton et al, 1986), the potential effectiveness of CA as a therapeutic for CNS diseases is limited to studies that have examined neuroprotection, anxiety, and erectile dysfunction (Kim et al, 2009; Kost et al, 2011, 2012; Sanna et al, 2013). To our knowledge, the present results are the first evidence that CA can disrupt rewarding and sensitizing effects of an addictive substance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These inconsistencies between CA and CTX in cocaine SA acquisition experiments suggest that the two β-lactam-containing compounds act through mechanisms that may not be entirely identical. One example is the increase in dopamine transmission produced by CA (Kost et al 2011; Sanna et al 2013). Some direct dopamine agonists display a profile similar to CA in that they decrease the breaking points under PR conditions but increase, or have no effect, on cocaine SA under FR reinforcement schedules (Depoortere et al 1993).…”
Section: Discussionmentioning
confidence: 99%